Optimal configuration of grid-side energy storage considering static security of power system - Tian, Xin; Zhao, Long; Tong, Chenjie; Meng, Xiangfei; Bo, Qibin; Chen, Yubing; Liu, Nian (Frontiers in Smart Grids, 2023)
The large-scale access of distributed power sources to the gird has brought great challenges to the safe and stable operation of the grid. At the same time, energy storage equipment is of great importance to effectively enhance the consumption of renewable energy and ensure the safe and stable operation of the grid. This paper proposes a method for optimal allocation of grid-side energy storage considering static security, which is based on stochastic power flow analysis under the semi-invariant method. Firstly, according to the load, wind power and photovoltaic probability model, a system stochastic power flow model is constructed. Furthermore, the fault probability and fault severity indicators are constructed from two dimensions of branch power flow and node voltage. And combine the fault probability and severity indicators to establish a static security assessment indicators system. Then, a grid-side energy storage planning model is constructed from the perspective of energy storage operators. Finally, a genetic algorithm is used to solve the two-stage planning and operation problem proposed in this paper, and simulation analysis is conducted based on the IEEE-30 node system to verify that the proposed energy storage allocation method can effectively improve the static security of the system.